Insulin-like growth factor type 1 concentrations in hyperthyroid cats before and after treatment with thiamazole. Issue 2 (February 2018) - Rochel, Daphné; Burger, Myriam; Nguyen, Patrick; Jaillardon, Laetitia
Objectives: The aim of this study was to evaluate changes in circulating insulin-like growth factor type 1 (IGF-1) concentrations in hyperthyroid cats, before and after thiamazole treatment. Methods: Thirty-four hyperthyroid cats were retrospectively included. Plasma free thyroxine (fT4) and IGF-1 concentrations were measured at diagnosis and 3 months after initiating antithyroid drug therapy. Results: Median fT4 significantly decreased ( P <0.001) after treatment (from 78 pmol/l [range 43–122 pmol/l] to 31 pmol/l [range below assay limit of detection to 88 pmol/l]), whereas IGF-1 values significantly increased ( P <0.001) after treatment (from 117 ng/ml [33–341 ng/ml] to 221 ng/ml [36–865 ng/ml]). fT4 and IGF-1 concentrations were significantly negatively correlated both at diagnosis (r = −0.43, P = 0.01) and after treatment (r = −0.51, P = 0.002). Conclusions and relevance: In cats, IGF-1 concentrations appear to be inversely proportional to the severity of hyperthyroidism and significantly increase after treatment with thiamazole.